2004
DOI: 10.1139/f04-088
|View full text |Cite
|
Sign up to set email alerts
|

Importance of landscape variables and morphology on nutrients in Missouri reservoirs

Abstract: The proportion of cropland cover in the catchments of Missouri reservoirs, a surrogate for non-point-source nutrient loss from agricultural watersheds, accounts for some 60%–70% of the cross-system variance in long-term averages of total phosphorus and total nitrogen (n = 126, ln transformation for nutrients and logit for cropland). The addition of dam height and an index of flushing rate improved r2 values to ~77% for both nutrients. Even among reservoir catchments with >80% grass and forest cover, croplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 33 publications
6
98
0
1
Order By: Relevance
“…Many other studies have also shown increases in TP in lakes related to the intensity of agricultural cultivation (Umbanhowar 2003, Jones et al 2004, Taranu and Gregory-Eaves 2008 and determinations of higher phosphorus exports with agricultural land as opposed to forested land (Endreny and Wood 2003).…”
Section: Lakementioning
confidence: 90%
“…Many other studies have also shown increases in TP in lakes related to the intensity of agricultural cultivation (Umbanhowar 2003, Jones et al 2004, Taranu and Gregory-Eaves 2008 and determinations of higher phosphorus exports with agricultural land as opposed to forested land (Endreny and Wood 2003).…”
Section: Lakementioning
confidence: 90%
“…Methods are detailed in Knowlton and Jones (1995) and Watanabe et al (2009). Reservoir morphology was determined from geographic information system (GIS) analysis (Jones et al 2004 or the Dam Safety Data Base (Missouri Department of Natural Resources 2011). Morphological metrics included surface area, maximum basin length, maximum effective length (MEL, greatest uninterrupted straight line distance along the reservoir main stem), and maximum effective width (MEW, greatest uninterrupted straight line distance from shore to shore perpendicular to the MEL axis).…”
Section: Datasets and Analysesmentioning
confidence: 99%
“…We also now understand that land cover (often agriculture) and lake or catchment morphometric characteristics (e.g., lake maximum depth, hydraulic flushing rates) are strongly related to nutrient concentrations and productivity in natural lakes and constructed reservoirs (Arbuckle and Downing 2001, Prepas et al 2001, Knoll et al 2003, Jones et al 2004, Bremigan et al 2008. Here, we focus on reservoirs because the effects of landscape disturbances may be especially pronounced in these waterbodies, which tend to have smaller surface water areas (Whittier et al 2002) and larger catchment area to surface water area ratios (CA:SA) compared to natural lakes (Kimmel et al 1990).…”
Section: Introductionmentioning
confidence: 99%